A study on health and the association between overweight/obesity and otorhinolaryngological diseases in 6- to 17-year-old children from Wrocław, Poland - Tomasz Zatoński; Katarzyna Pazdro-Zastawny; Mateusz Kolator; Joanna Krajewska; Alicja Basiak-Rasała; Sara Górna; Michał Zatoński (Archives of Medical Science, 2020)
Introduction Childhood overweight and obesity have become a global problem in the past three decades. There are very few studies which examine the correlation between body mass index (BMI) and the development of otorhinolaryngological diseases in children. The objective of the study was to determine the association between overweight or obesity in children and the occurrence of otorhinolaryngological diseases.